ANALISIS GERAKAN LITERASI SEKOLAH UNTUK MENUMBUHKAN KARAKTER GEMAR MEMBACA SISWA - Rahma, Anisa Nur; Purnomo, Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to initiate an understanding of how the implementation of the School Literacy Movement (GLS) can shape the character of students who grow through the cultivation of reading habits. GLS is a strategic program initiated by the Ministry of Education and Culture to encourage students to read for 15 minutes every day in the school environment (Kemendikbud, 2016; Nugrahini, 2021). This study uses a qualitative approach, using data collection techniques in the form of observation, interviews, and documentation involving teachers, principals, and students as research subjects (Nismawati, 2024; Guthrie & Klauda, ​​​​2014). The results of the study showed that the implementation of GLS was effective in increasing students' interest in reading while fostering a love of reading through the stages of habituation, development, and integration of literacy activities into school routines (Sari & Wulandari, 2020; Gambrell, 2011). In addition to improving literacy skills, GLS also functions as an effective means of instilling positive character values, encouraging students to become lifelong learners.